2023
DOI: 10.1186/s12906-023-04137-y
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxic effect of stigmasterol derivatives against breast cancer cells

Nondumiso Premilla Dube,
Vuyelwa Jacqueline Tembu,
Getrude R Nyemba
et al.

Abstract: Background Stigmasterol is an unsaturated phytosterol that belong to the class of tetracyclic steroids abundant in Rhoicissus tridentata. Stigmasterol is an important constituent since it has shown impressive pharmacological effects such as anti-osteoarthritis, anticancer, anti-diabetic, anti-inflammatory, antiparasitic, immunomodulatory, antifungal, antioxidant, antibacterial, and neuroprotective activities. Furthermore, due to the presence of π system and hydroxyl group, stigmasterol is readi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Research suggests that stigmasterol has anti-inflammatory, antioxidant, and anticancer effects [28]. In a study, Dube et al [29] synthesized eight derivatives of stigmasterol and explored their antibreast cancer activity against the HCC70 cell line. They concluded that structural analogues of this phytochemical after modifications in functional groups can improve anticancer activity, and the compound and its derivatives have potential as lead anticancer drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that stigmasterol has anti-inflammatory, antioxidant, and anticancer effects [28]. In a study, Dube et al [29] synthesized eight derivatives of stigmasterol and explored their antibreast cancer activity against the HCC70 cell line. They concluded that structural analogues of this phytochemical after modifications in functional groups can improve anticancer activity, and the compound and its derivatives have potential as lead anticancer drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Phytosterols are bioactive substances occurring naturally in various plants. Stigmasterol (STIG), a phytosterol, is abundant in several plants [ 17 ], and it exhibits a range of pharmacological effects, including antioxidant [ 18 ], anti-cancer [ 19 ], and anti-inflammatory properties [ 20 ]. Regarding melanoma, it has been reported that STIG has cytotoxic effects on human malignant melanoma cell lines [ 21 ] and mouse malignant melanoma (B16F10) cell lines [ 22 ].…”
Section: Introductionmentioning
confidence: 99%